2019
DOI: 10.1029/2019jg005022
|View full text |Cite
|
Sign up to set email alerts
|

Linking In Situ Photochemical Reflectance Index Measurements With Mangrove Carbon Dynamics in a Subtropical Coastal Wetland

Abstract: Photochemical reflectance index (PRI) has been found to be closely related with vegetation photosynthetic phenology in many ecosystems including boreal evergreen, but its ability to track carbon dynamics in low‐latitude evergreen mangrove ecosystems has rarely been assessed. To fill up this gap, this paper explored potential mangrove PRI‐carbon links and their environmental controls across temporal scales (diurnal and seasonal), based on 1‐year continuous high‐resolution (half‐hourly) time series measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 63 publications
7
15
0
Order By: Relevance
“…The seasonal variation patterns of PRI0 and sunlit PRI were consistent across years (Figure 6), which implied that the size of the pigment pool was affected by seasonal variations of environmental factors [38], in particular for PAR. This is consistent with a previous study showing that PRI was radiation-dominated with additional effects from high VPD [42]. The typical seasonal variations of subtropical mangrove forests have higher and lower PAR in summer and winter, respectively [42], leading to similar seasonal variations of two components of PRI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The seasonal variation patterns of PRI0 and sunlit PRI were consistent across years (Figure 6), which implied that the size of the pigment pool was affected by seasonal variations of environmental factors [38], in particular for PAR. This is consistent with a previous study showing that PRI was radiation-dominated with additional effects from high VPD [42]. The typical seasonal variations of subtropical mangrove forests have higher and lower PAR in summer and winter, respectively [42], leading to similar seasonal variations of two components of PRI.…”
Section: Discussionsupporting
confidence: 92%
“…Although some attempts have been made to focus on this issue [40,41], most lack long-term continuous measurements that are necessary for clarifying the relationship between PRI and mangrove carbon fluxes at both seasonal and inter-annual time scales. Zhu et al [42] explored the link between PRI and mangrove carbon dynamics at a seasonal scale but they were not able to reveal any inter-annual variation pattern. Here, based on four-years of continuous measurement of mangrove PRI and EC-based ecosystem carbon fluxes, the purposes of this study are (1) to analyze the response of mangrove carbon fluxes to climate fluctuations and drought stress, (2) to examine the ability of PRI to track the response of the mangrove carbon cycle to climatic anomalies, and (3) to explore the complex mechanisms underlying PRI variations across different time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Raw EC data were recorded by a CR3000 data logger (Campbell Scientific, Inc.) at 10 Hz. A typical EC pre-processing procedure, including flux calculations, corrections and quality controls (see Zhu, Song, et al (2019) for details), was implemented in the Ed-dyPro6.1 software (Li-COR Inc.) to produce half-hourly time series of NEE. Co-spectral analysis confirmed that the EC system was able to capture eddy fluxes of CO 2 across the whole range of frequencies (Figure S1).…”
Section: Eddy Covariance Meteorological and Tidal Measurementsmentioning
confidence: 99%
“…Here, the mass balance model of carbon flow through the world's mangrove ecosystems constructed by Alongi [2] is revised, using the data in Sections 2.1-2.3 and in Table 2, and newer data for soil + root burial [3,106], root production [107], mangrove gross primary production (GPP), POC, and DOC export [7,10], and canopy respiration (R c ) [19,66,[108][109][110][111][112][113][114], and extrapolated using the most recent estimate of global mangrove area [115]. The revised carbon flow model ( Figure 5) shows that ∼64% of GPP is respired by the canopy with NPP vested nearly equally in the litter, wood, and belowground root production.…”
Section: Carbon Flow Through the World's Mangrove Ecosystems And Contmentioning
confidence: 99%